Disability Servitude From Peonage to Poverty - Beckwith, Ruthie-Marie.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Disability Servitude traces the history of peonage unpaid, forced labor by people with disabilities in public and private institutions. Describing the work they performed and lawsuits filed to get paid, it links that history with the continued segregation and exploitation of workers with disabilities that are paid far less than minimum wage.
Keywords: Science; Science; Science, general; Electronic books